Fracture modes in micropillar compression of brittle crystals - Howie, Philip R.; Korte, Sandra; Clegg, William J. (Journal of Materials Research, 2012)
This article describes cracking during microcompression of Si, InAs, MgO, and MgAl 2O 4 crystals and compares this with previous observations on Si and GaAs micropillars. The most common mode of cracking was through-thickness axial splitting, the crack growing downward from intersecting slip bands in pillars above a critical size. The splitting behavior observed in all of these materials was quantitatively consistent with a previous analysis, despite the differences in properties and slip geometry between the different materials. Cracking above the slip bands also occurred either in the side or in the top surface of some pillars. The driving forces for these modes of cracking are described and compared with observations. However, only through-thickness axial splitting was observed to give complete failure of the pillar; it is, therefore, considered to be the most important in determining the brittle-to-ductile transitions that have been observed. © 2011 Materials Research Society.
Created from Fastlane, Scopus look-up
Keywords: Ceramic; Fracture; Toughness